Dynamic of a planing hull in regular waves: Comparison of experimental, numerical and mathematical methods. (1st December 2020) - Tavakoli, Sasan; Niazmand Bilandi, Rasul; Mancini, Simone; De Luca, Fabio; Dashtimanesh, Abbas
Abstract: The unsteady planing motion in waves is a complicated problem, that can lead to uncomfortable riding situation and structural damages due to large wave-induced dynamic responses and vertical accelerations. In the current research, this problem is investigated using different approaches, including towing tank tests, Computational Fluid Dynamics (CFD), and the 2D +  t model. Results obtained from all three approaches are compared against each other in details. The spectral analysis shows that all motions can be nonlinear, but CFD and 2D +  t model may predict weaker nonlinear behaviour at higher speed, especially for the case of vertical accelerations corresponding to longer waves. Interestingly, the vertical acceleration found by 2D +  t model is seen to be under-predicted at moderate and long wavelengths and to be over-predicted at short waves. The values of sectional forces found by 2D +  t model were compared against CFD results, showing that, while the 2D +  t model computes smaller sectional forces, it can also compute negative sectional forces near the bow of the vessel at short waves when the boat exits the water. The emergence of negative sectional forces is likely to be the reason why the 2D +  t model over-predicts the vertical acceleration in short waves. Highlights: Seakeeping test for 8 regular wave conditions for the C2 hull of Naples Systematic Series. Comparison between experimental data, 2D + t results, and CFD U-RANSE simulations. Output values are heave, pitch angle, vertical acceleration, and added resistance. CFD U-RANSE and 2D + t method predict weaker nonlinear behaviour at higher speed. Overall good capability of CFD U-RANSE and 2D + t method to predict the hull resistance in waves.